Restrictions on Cross-Border Trade in E-Commerce as a Form of Consumer Protection - Yuyut prayuti (JILPR Journal Indonesia Law and Policy Review, 2023)
Since the beginning of the third millennium era, the world of commerce has experienced a significant evolution with the emergence of e-commerce platforms. Bank Indonesia estimates that e-commerce transactions in 2022 will reach Rp489 trillion. Correspondingly, in Q3 2022, it was recorded that 62.6% of internet users over the age of 16 have used e-commerce platforms to purchase products and services online, increasing the potential for discrepancies between product descriptions and reality, as well as difficulties in returning products from abroad, resulting in financial losses and dissatisfaction for consumers. This research aims to investigate the effectiveness of cross-border trade restrictions in e-commerce as a consumer protection strategy in Indonesia. The normative juridical method is used in this research. The research found that restrictions on cross-border trade in e-commerce refer to various barriers and regulations applied by states to govern cross-border electronic commerce activities. These barriers include tariffs, taxes, quotas, product quality standards, certification, etiquette, as well as rules regarding consumer personal data and payment transactions. In addition, in the era of globalization, trading cross-border transactions has become routine, but carries legal and commercial risks for consumers transacting with entities outside their jurisdiction. Therefore, to respond to the escalation of cross-border trade in e-commerce platforms, Indonesia needs to emphasize data protection and security in digital transactions such as related to cryptographic techniques and privacy policies of e-commerce providers in order to provide certainty and legal protection in terms of protecting consumers.